The Planning Role in Stretching the City A Tale of Two London Neighbourhoods - Flint Ashery, Shlomit (Cham : Springer International Publishing : Imprint: Springer, 2023)
This research aims to uncover new insights into minority housing strategies and their impact on densely populated urban areas. The study assumes that as space becomes scarce, inter and intra groups interactions in the urban space motivate people to maximize the utility of the resources at their disposal. This 'stretch' of the built environment provides them with critical selective advantages and a sense of security and belonging. Based on two neighbourhoods in London, it contributes to our understanding of housing decisions in the context of illegality and shows the capacity of a given urban form for adaptation: It creates a new semi-private/public space, partly segregated yet deeply integrated; a sphere that, on the one hand, enables traditional 'nested' places and, on the other, a fertile environment for integration. This manuscript contributes two new ideas to the knowledge base of residential selections and the geography of opportunities. The first is a detailed analysis of a hyper-segregation/integration pattern resulting from complementary residential strategies operating at the individual unit level. The second is multidimensional stretching, a bottom-up initiation that allows individuals to maximize resources through territorial and spatial practices.
Introduction -- 1) Approaches to social-residential relations -- 2) Methodology -- 3) Managing residential selections in the context of illegality -- 4) Legal status as a cause for Residential constraints -- 5) Ethnicity as a bridge between Stated and Revealed residential preferences -- 6) The effect of different compositions of social ties on residential selections -- 7) Ties between undocumented individuals of the same community -- 8) Ties between undocumented individuals of different communities -- 9) Ties between undocumented and documented individuals of the same community -- 10) Ties with documented individuals of different communities -- 11) Conclusion.
Keywords: Human geography; Cultural geography; Cities and towns -- History; Human physiology; Emigration and immigration -- Social aspects; Urban policy; Social and Cultural Geography; Urban History; Human Physiology; Sociology of Migration; Human Geography; Urban Policy